1988
DOI: 10.1080/00223980.1988.9915520
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in Abortion Attitudes: 1975-1980-1985

Abstract: In this study, we compared the attitudes toward abortion of respondents from the National Opinion Research Center's (NORC) General Social Survey (GSS) for the years 1975, 1980, and 1985. The major theme of the GSS is that an adequate description of changes in abortion attitudes is predicted on resolving the question of whether the six abortion items used in the surveys measure one or two dimensions. We used the Mokken method of scale analysis, a stochastic extension of Guttman scaling, to resolve this question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Studies have consistently found more support for abortion in cases of a woman’s poor mental or physical health, rape, or fetal anomaly, than in cases of financial hardship, relationship troubles, or other difficult life circumstances. (Gillespie, Ten Vergert, & Kingma, 1988)(Bane et al, 2003)(Cook, Jelen, & Wilcox, 1993) (Smith & Son, 2013) (Hans & Kimberly, 2014) Individual attitudes on abortion are complex and sometimes appear contradictory: e.g., among respondents who say abortion is murder and/or morally wrong, many also say it should be an individual choice left to a woman and her doctor. (Cox et al, 2011) (Moral Issues: Gallup Historical Trends 2014)(Newport & Bird, 2017) Even many Americans who believe that life begins at conception find legal abortion acceptable in many situations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have consistently found more support for abortion in cases of a woman’s poor mental or physical health, rape, or fetal anomaly, than in cases of financial hardship, relationship troubles, or other difficult life circumstances. (Gillespie, Ten Vergert, & Kingma, 1988)(Bane et al, 2003)(Cook, Jelen, & Wilcox, 1993) (Smith & Son, 2013) (Hans & Kimberly, 2014) Individual attitudes on abortion are complex and sometimes appear contradictory: e.g., among respondents who say abortion is murder and/or morally wrong, many also say it should be an individual choice left to a woman and her doctor. (Cox et al, 2011) (Moral Issues: Gallup Historical Trends 2014)(Newport & Bird, 2017) Even many Americans who believe that life begins at conception find legal abortion acceptable in many situations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported significant increases in the approval of legalized abortion between 1965 ad 1975, the largest shift occurring between 1965 and 1970 (Beniger, 1984;Granberg & Granberg, 1985). Researchers that compared between 1'}75 and 1980 reported less change (Ebaugh & Haney, 1980;Granberg & Granberg, 1980), and a small though significant drop in approval from 1980(Gillespie, Vergert and Kingma, 1988.…”
Section: Referencesmentioning
confidence: 96%
“…For the purpose of this study all the items were considered as unidimensional based on Gillespie, Vergert, and Kingma (1988) use ofMokken method of scale analysis indicating their unidimensionality. They concluded that the scale was robust across the three periods studied.…”
Section: Index Construction I Unidimensionalitymentioning
confidence: 99%
“…Much of the research on abortion attitudes has used data taken from the National Opinion Research Center's General Social Surveys. These studies have consistently revealed that abortion approval varies greatly depending on the reason (e.g., Cook et al, 1992;Ebaugh & Haney, 1980;Gillespie, Ten Vergert, & Kingma, 1988;Granberg & Granberg, 1980;Jelen, 1988). For example, abortion due to a rape is more approved of than abortion because the woman does not want any more children.…”
Section: Causes and Attitudesmentioning
confidence: 99%